The Model of Integrated Knowledge and Skills of the Future Lawyers - Savka, Iryna (Pedagogical Discourse, 2016)
Ключові слова: інтегрований курс, модель професійної спрямованості підготовки, загальнопедагогічні принципи, методологічні підходи, інтегративний підхід, професійна спрямованість підготовки. The article suggests the model of training of future lawyers. The proposed model in this study involves the integration of humanities and professional disciplines. The judgments about the fundamental nature of the humanities in the training of future lawyers and their professional orientation are the basis of the model. The purpose of the model is to increase the readiness for future lawyers to the profession. The use of this model makes it possible to improve the success of training of future lawyers. The model of professionally oriented humanitarian training of the future lawyers is drafted which enhances the educational potential of foreign language education of the students. The use of this model makes it possible to increase the level of the successful training of future lawyers. The main methodological approaches to the formation of professionally directed training of future lawyers are selected. The teaching principles that enhance the level of professionally directed training of future specialists in law are highlighted. They are: the interdisciplinary communication, the integration of knowledge and skills, the content profiling, succession in studying, the continuity of learning. A number of conceptual principles are determined, in particular the development of integrated conceptual vision of the content of the training of future specialists in law based on the principles of educational philosophy, methodology, pedagogy, the use of the systematic, active, cognitive and personality-based approaches; the improvement of the quality of professional training of future law experts and its compliance with the requirements of the modern society that demands the integration processes of the learning content . The basic methodological approaches to modeling professionally directed training of future lawyers are stated. The principles of general professional orientation humanitarian training of future lawyers in higher education based on an integrative approach are highlighted. A professionally-directed discipline «Law with the elements of Political science and Country studies» is suggested. Key words: integrated course, the model of the professionally orientated training, general principles, methodological approaches, integrative approach, professional orientation training.